2014
DOI: 10.1136/bcr-2014-205036
|View full text |Cite
|
Sign up to set email alerts
|

Critical airway involvement in relapsing polychondritis

Abstract: Relapsing polychondritis (RP) is a rare multisystem disease characterised by progressive inflammation and destruction of cartilaginous structures. Airway involvement in RP occurs in approximately 50% of cases. We present a 70-year-old woman with a diagnosis of early adult onset asthma. She required multiple hospital admissions for recurrent episodes of acute severe dyspnoea for 1 year. These were treated as asthma. Months later she developed saddle nose deformity and hoarseness of voice. CT revealed tracheal/b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Multivariate analysis of 142 cases of RP with tracheal chondritis found that although tracheal chondritis was not a major cause of death, infectious diseases were common and were responsible for admission to intensive care 13 . Some previous reports of cases that initially occurred in the respiratory tract found that 5 of 11 patients required tracheostomy and three required stent placement, and four of these died of respiratory failure or pneumonia 14‐22 . This suggests that airway chondritis requiring local treatment, such as tracheostomy or stenting, has a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis of 142 cases of RP with tracheal chondritis found that although tracheal chondritis was not a major cause of death, infectious diseases were common and were responsible for admission to intensive care 13 . Some previous reports of cases that initially occurred in the respiratory tract found that 5 of 11 patients required tracheostomy and three required stent placement, and four of these died of respiratory failure or pneumonia 14‐22 . This suggests that airway chondritis requiring local treatment, such as tracheostomy or stenting, has a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory disturbance results from airway collapse secondary to destruction of tracheal rings or narrowingof the tracheal lumen caused by fibrous or inflammatory edema. Airway manifestations are the commonest cause of morbidity and mortality in the disease 6 . The management of respiratory tract involvement in relapsing polychondritis is important because sudden respiratory arrest mayoccur 5 , as manifested by an acute episode of choking in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of early diagnosis of airway involvement in relapsing polychondritis can lead to irreversible cartilage damage. Steroids or other immunosuppressants are ineffective in these advanced cases, and would require airway interventions such as tracheostomy or tracheobronchial stents 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relapsing polychondritis (RP) is a rare, autoimmune, multisystem disease characterized by antibodies to type II collagen in its pathogenesis, which is accompanied by episodic inflammatory attacks in articular and non-articular cartilage tissue [1,2]. Airway manifestations are the most comment cause of morbidity and mortality in the disease [3].…”
Section: Introductionmentioning
confidence: 99%